Preyssler-type phosphotungstate is a new family of negative-staining reagents for the TEM observation of viruses - Koichi Sahiro; Yasuhiko Kawato; Kanae Koike; Tsuneji Sano; Toshihiro Nakai; Masahiro Sadakane (Scientific Reports, 2022)
Abstract Transmission electron microscopy (TEM) is an essential method in virology because it allows for direct visualization of virus morphology at a nanometer scale. Negative staining to coat virions with heavy metal ions must be performed before TEM observations to achieve sufficient contrast. Herein, we report that potassium salts of Preyssler-type phosphotungstates (K(15-n)[P5W30O110Mn+], M = Na+, Ca2+, Ce3+, Eu3+, Bi3+, or Y3+) are high-performance negative staining reagents. Additionally, we compare the staining abilities of these salts to those of uranyl acetate and Keggin-type phosphotungstate. The potassium salt of Preyssler-type phosphotungstates has the advantage of not requiring prior neutralization because it is a neutral compound. Moreover, the potassium counter-cation can be protonated by a reaction with H+-resin, allowing easy exchange of protons with other cations by acid–base reaction. Therefore, the counter-cations can be changed. Encapsulated cations can also be exchanged, and clear TEM images were obtained using Preyssler-type compounds with different encapsulated cations. Preyssler-type phosphotungstates may be superior negative staining reagents for observing virus. Polyoxotungstates (tungsten-oxide molecules with diverse molecular structures and properties) are thus promising tools to develop negative staining reagents for TEM observations.